PEMIKIRAN POLITIK ISLAM DALAM PERSPEKTIF SEJARAH - Ghafur, Muhamad fFakhry (Jurnal Penelitian Politik, 2011)
The History ofIslamic Political Thought can be divided into three periods The Classical period tookplacefrom Muhammad era until 1250 M characterized by the rule ofKhalifah as public servant The Middle periodexisted until 1800 where Khilafah was camouflage for the real kingdom and descendants of Quraisy Last TheModern Period let the western values to including modern political theory The article is to review the topic in thebook especially the issue ofperiodization